Dedication earns Sisneros big state National Guard job - Ferrendelli, Betta (Raton Range Raton, New Mexico, 1990)
Newspaper Article on the promotion from commander of the 6th Battalion 200th Air Defense Artillery in Springer to director of resource management at the New Mexico Army National Guard Headquarters in Santa Fe, New Mexico.
Master list item #: 13
File location is in the Raton File Cabinet
Keywords: Sisneros, Gene; Baca, Edward; Stevens, Velton; Archibeque, Carlos A; Morrow, Thomas; National Guard; U.S. Army; Local History; Biography; Life and Customs; Promotion; National Guard -- Commander; Resource Management; 6th Battalion 200th Air Defense Artillery; Patriotic; Troops; Raton, New Mexico; Springer, New Mexico; Santa Fe, New Mexico